Motif Warm-glow dan Kepuasan Petani Berusahatani Organik: Kasus di Pulau Jawa - Muntoro Muntoro; Irham Irham; Jangkung Handoyo Mulyo; Any Suryantini (Manajemen Agribisnis: Jurnal Agribisnis, 2022)
The main objective of developing organic agriculture should not deviate from the principles of organic agriculture which include economics, health and the environment. However, there is often a trade off between the three main objectives. It was found that organic farmers in developed countries prioritize non-economic goals such as health and environmental sustainability. And vice versa with organic farmers in developing countries. However, there are a few organic farmers in developing countries who still survive, coming from indigenous peoples or ethnic groups who are considered backward. This is because there is a warm-glow motif which is interpreted as happiness and pleasure in doing good.